(3JfejI egGQGJ GdJYde GdefXe PGJjG (B=s Developing self-regulated learning skills - (3Ydj, ejQaJ eMehO eMeOs ((3YeGf (B- (3GdCQOf (B:s (3eQcR OjHhfh dJYdje GdJacjQ,s, 2018)
(3jYO cJGH (B((3JfejI egGQGJ GdJYde GdefXe PGJjG(B) (3hGdJj bGeJ HJCdjag (B((3O(B. (3ejQaJ eMehO eMeO Ydj(B) (3CMO GdCSGdjH GdMOjKI hGdegeI aj JOQjH GdJdGejP Ydi cjajI GcJTGa GdeYdheGJ hagegG hGdJYGed eYgG, habG dbOQGJ hGSJYOGOGJ cd JdejP, hEf GdJYde GdefXe PGJjG YedjI HhGSWJgG jSJWjY GdWdGH GSJNOGe GSJQGJjLjGJ eYjfI dJMbjb CgOGa CcGOjejI Ydi CSGS EOQGc aGYdjI GdPGJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B147-153.s
Keywords: (3GdJYdje GdPGJjs -- (3WQb JOQjSs